A Critique of the Right Intention Condition as an Element of Jus ad Bellum. Issue 1 (2nd January 2016) - Janzen, Greg
ABSTRACT: According to just war theory, a resort to war is justified only if it satisfies the right intention condition. This article offers a critical examination of this condition, defending the thesis that, despite its venerable history as part of the just war tradition, it ought to be jettisoned. When properly understood, it turns out to be an unnecessary element of jus ad bellum, adding nothing essential to our assessments of the justice of armed conflict.